Com a palavra, as professoras coordenadoras: o EMAI na formação contínua de docentes em matemática - Ayres, Regina Helena Reis Souza (2021)
The Department of Education of the State of São Paulo, concerned with the process of teaching and learning mathematics in its schools, implements in 2012 a public policy focused on the teaching of mathematics, the EMAI Project (Mathematics Education in the Early Years), which proposes to articulate actions of curriculum development, teacher training in service and evaluation of students. This study sought to understand how pedagogical coordinators see the didactic guidelines present in the EMAI, further: whether and how they are used to support the training of multipurpose teachers in Mathematics. The research, of a qualitative nature, employed semi-structured interviews to collect data from three Pedagogical Coordinators linked to two Regional Teaching Boards located in São Paulo city's metropolitan region. The data were organized in a posteriori axes and analyzed according to the guidelines of the Cycle Approach (BALL; BOWE, 1992) and the light of the EMAI theoretical framework. The results revealed that the participants understand the EMAI texts and find their authors innovative, even feeling like co-authors for participating in its initial elaboration. The PC also made criticisms. It is worth noting that they consider EMAI to be a school project and not a public policy and pointed out that its training model is inadequate for understanding the project's purposes and, for this reason, preventing in-depth discussions. The participants stated that the Project allowed the development of a more organized formative practice with decisions made in the collective allowing the construction of bonds between the participants. The results also showed that the teaching of mathematics in the schools of the Network has used approaches that do not favor reflection. This fact and the outdated curricula of the Faculties of Education seem to be responsible for the teachers' difficulty understanding the contents of the EMAI. Thus, it is recommended that the Regional Teaching Boards offer, through the Coordinating Teachers of the Pedagogical Centers in them, more and better training for the Pedagogical Coordinators, who are in the educational establishments, providing them with full knowledge about the EMAI and training him to teach the teachers at this specific school system